Description of the nikolskii-besov class decreasing its smoothness parameter using weak fractional derivatives (2013)
The Nikolskii-Besov spaces Bpqα(Rn)≡ Bpqα, 1≤ p, q≤∞, α and gt;0, recently were described using the Caputo's fractional derivative. Using the concept of weak fractional derivative, in this paper we reduces the characterization of Bpqα to the case Bpqγ, where γ is any positive number strictly less than α.